2019
DOI: 10.1002/qj.3445
|View full text |Cite
|
Sign up to set email alerts
|

A dynamic extension of the pragmatic blending scheme for scale‐dependent sub‐grid mixing

Abstract: A recent pragmatic blending approach treats sub-grid turbulent mixing using a weighted average of a 1D mesoscale model and a 3D Smagorinsky formulation. Here the approach is modified and extended to incorporate a scale-dependent dynamic Smagorinsky scheme instead of a static Smagorinsky scheme. Results from simulating an evolving convective boundary layer show that the new scheme is able to improve the representation of turbulence statistics and potential temperature profiles at grey-zone resolutions during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…However, the diffusive nature of the Smagorinsky scheme can result in the delayed spin‐up of nonlocal motions especially during the handover from the nonlocal mesoscale to the Smagorinsky scheme in deepening CBLs, as shown in Efstathiou et al (2016). Efstathiou and Plant (2019) extended the blending approach by incorporating a scale‐dependent dynamic Smagorinsky scheme instead of the standard static Smagorinsky scheme. They found some promising results in idealized simulations of an evolving CBL, particularly in relation to the spin‐up of resolved turbulence (cf.…”
Section: Modeling the Abl In The Gray Zone Of Turbulencementioning
confidence: 99%
See 1 more Smart Citation
“…However, the diffusive nature of the Smagorinsky scheme can result in the delayed spin‐up of nonlocal motions especially during the handover from the nonlocal mesoscale to the Smagorinsky scheme in deepening CBLs, as shown in Efstathiou et al (2016). Efstathiou and Plant (2019) extended the blending approach by incorporating a scale‐dependent dynamic Smagorinsky scheme instead of the standard static Smagorinsky scheme. They found some promising results in idealized simulations of an evolving CBL, particularly in relation to the spin‐up of resolved turbulence (cf.…”
Section: Modeling the Abl In The Gray Zone Of Turbulencementioning
confidence: 99%
“…Some promising results have emerged from both major categories. Some simple blending/hybrid schemes using nonlocal turbulence (Boutle et al, 2014; Efstathiou & Plant, 2019; Shin & Hong, 2015), TKE (Ito et al, 2015; Zhang et al, 2018), or mass‐flux approaches (Honnert et al, 2016) may significantly improve the representation of first‐order quantities and turbulence statistics in the CBL gray zone.…”
Section: Modeling the Abl In The Gray Zone Of Turbulencementioning
confidence: 99%
“…Deriving partitioning functions of turbulence fluxes in gray zone is of particular significance to represent the scale dependency of SGS transport. This is because such functions can aid in blending local/nonlocal heat fluxes (Shin & Hong, 2015;Zhang et al, 2018), mixing or dissipation length scales (Boutle et al, 2014;Efstathiou & Beare, 2015;Zhang et al, 2018), or eddy diffusivity coefficients (Efstathiou et al, 2016;Efstathiou & Plant, 2019) between mesoscale and microscale, required for the development of gray zone parameterizations. However, these attempts have been limited to solely address the scale dependency of TKE and vertical heat flux since the earliest study of Honnert et al (2011) and later in Sin and Hong (2013Hong ( , 2015, Boutle et al (2014), and Kurowski and Teixeira (2018).…”
Section: Introductionmentioning
confidence: 99%
“…Efstathiou et al (2016) followed this approach but applying to the CBL in terms of different convective forcings. Efstathiou and Plant (2019) further modified this model in blending the YSU PBL scheme with the dynamic Smagorinsky SGS model (Bou‐Zeid et al, 2005). They found that the use of dynamic Smagorinsky model outperforms that of standard Smagorinsky model (Smagorinsky, 1963) for the blending in gray zone grid spacings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation